2006
DOI: 10.1053/j.jrn.2005.10.013
|View full text |Cite
|
Sign up to set email alerts
|

A Simple Nutrition Screening Tool for Hemodialysis Nurses

Abstract: The tool was more sensitive and specific than the NST previously reported by the same investigators. The tool is particularly specific in that it screens those patients not requiring dietitian intervention. The use of this tool may benefit HD units that do not have on-site or regular dietetic support to prioritize patients needing dietitian intervention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 16 publications
1
5
0
Order By: Relevance
“…Previous research using the four‐item satellite dialysis nutrition screening tool has identified its relatively high sensitivity and specificity when compared with the gold standard subjective global assessment (Bennett et al . ). Using an RCT method, this study has supported the hypothesis that more patients will be referred using this screening tool.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…Previous research using the four‐item satellite dialysis nutrition screening tool has identified its relatively high sensitivity and specificity when compared with the gold standard subjective global assessment (Bennett et al . ). Using an RCT method, this study has supported the hypothesis that more patients will be referred using this screening tool.…”
Section: Discussionmentioning
confidence: 97%
“…The tool that we used has been previously validated in an Australian haemodialysis population (n = 112) and exhibited a sensitivity of 0Á84 (range, 0Á71-0Á94; p < 0.05) and a specificity of 0Á9 (range, 0Á82-0Á98; p < 0.05) (Bennett et al 2006). This tool was chosen because of its simplicity and because it is the only screening tool that we are aware of that has been validated in the satellite haemodialysis population.…”
Section: Interventionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this study, we found no effect of a combined education and incentives programme on participant serum phosphate which is consistent with a recent education and incentivisation intervention (Chow & Dalton ). Dietician‐led education programmes have demonstrated decreased phosphate levels (de Brito Ashurst & Dobbie ; ); however, not all dialysis centres have access to renal‐specific dieticians, particularly centres in developing countries (). Nephrologist‐led education interventions have also been successful in reducing phosphate levels ().…”
Section: Discussionmentioning
confidence: 99%